PENGARUH PAJAK, KEPEMILIKAN ASING, DAN TUNNELING INCENTIVE TERHADAP KEPUTUSAN TRANSFER PRICING - Restu, Yuliana; Ambarita, Dinar (Jurnal Nusa Akuntansi, 2024)
This study aims to determine Tax, foreign ownership, and tunneling incentives on transfer pricing. The population in this study are consumer non-cyclical companies listed on the Indonesia Stock Exchange (IDX). The research method used in this study is a quantitative method with secondary data and sample selection in this study using the purposive sampling method. The total number of samples in this study is 7 consumer non-cyclical companies as research samples. The analysis method used in this study using panel data regression analysis with the help of the e-views software program version 12. The results of the study indicate that together or simultaneously stating Tax, foreign ownership and tunneling incentives have an influence on companies to carry out transfer pricing, partially tax does not have a significant influence in influencing transfer pricing decisions. In terms of foreign ownership does not affect transfer pricing decisions. Partially tunneling incentives affect transfer pricing